Research friction surface grader blades with ion-plasma coating - Венцель, Є.С.; Щукін, О.В. (Problems of Tribology, 2016)
The use of ion plasma coating TiN-Cr2N thickness of 4 micrometers by condensation of ion bombardment can in-crease the wear resistance of cutting elements graders steel 65G 2 times, maintain the geometrical shape of the knife, as well as the value of the toughness of the material from which it is made. The main goal of the research was to determine the reasons for the increase of wear resistance of the cutting ele-ments graders. Metallographic studies were performed using a microscope MIM-8 500 increases, 1000, followed by photograph-ing an image. As a result metallographic investigations we have found that Cr2N-TiN coating has the best adhesion with a thickness of 2 to 5 microns, otherwise there is a violation of the integrity of the surface layer. As a result of electron microprobe analysis, it was found that the portion of titanium is prevalent in the coating. The method of quality X-ray analysis, which was conducted by setting the MSD 50 allowed to trace the distribution of chemical elements in the coating of TiN-Cr2N, the transition zone and the matrix, as well as to identify the inclusion of various kinds. The results of X-ray and micro X-ray spectral studies have shown that increasing the wear-resistant coatings TiN-Cr2N, established at the optimum value of thickness 4 microns, due to the presence of titanium and corrosion resistance - chrome.